2017
DOI: 10.1007/s10695-016-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing fish meal with rubber seed meal on growth, nutrient utilization, and cholesterol metabolism of tilapia (Oreochromis niloticus × O. aureus)

Abstract: A feeding trial was conducted to evaluate the effects of replacing fish meal with rubber seed meal (RSM) on growth, nutrient utilization, and cholesterol metabolism of tilapia (Oreochromis niloticus × Oreochromis aureus). Five experimental diets were formulated with 0, 150, 300, 450, and 600 g kg RSM replacing graded levels of fish meal, respectively. Each diet was randomly assigned to triplicate groups of 25 fish (initial average weight 65.3 g) per aquarium in a rearing system maintained at 29 ± 1 °C for 8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
5
0
1
Order By: Relevance
“…Similar to our results, replacing fish meal protein with PSC protein did not significantly decrease the intake of the PSC-containing diet compared to that of the reference diet in O. mykiss (Greiling et al, 2018). Similarly, the inclusion of a rubber seed meal instead of SBM did not affect the feed intake of tilapia (Deng et al, 2017). In this study, the best FCR value was observed in the PSC66 treatment, and this positive result was also detected for WG and SGR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our results, replacing fish meal protein with PSC protein did not significantly decrease the intake of the PSC-containing diet compared to that of the reference diet in O. mykiss (Greiling et al, 2018). Similarly, the inclusion of a rubber seed meal instead of SBM did not affect the feed intake of tilapia (Deng et al, 2017). In this study, the best FCR value was observed in the PSC66 treatment, and this positive result was also detected for WG and SGR.…”
Section: Discussionsupporting
confidence: 88%
“…mykiss (Greiling et al, 2018). Similarly, the inclusion of a rubber seed meal instead of SBM did not affect the feed intake of tilapia (Deng et al, 2017). In this study, the best FCR value was observed in the PSC66 treatment, and this positive result was also detected for WG and SGR.…”
Section: Discussionmentioning
confidence: 99%
“…Another response that favored the inclusion of MPM in diets was the enzymatic activity that is involved in amino acid metabolism (liver transamination), which did not alter its activity at the different inclusion levels. In tilapias, reductions of aspartate aminotransferase (AST) activity were observed in plant-based diets and it was suggested that the reduction occurs by distancing the nitrogen products from the oxidative pathways (Deng et al, 2017). In addition to plant sources, Xiong et al (2014) observed that high protein/ starch ratios increased AST activities.…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar bahan baku untuk produksi pakan ikan hingga saat ini masih tergantung pada impor (GPMT, 2015). Upaya untuk mengurangi ketergantungan ini adalah dengan memanfaatkan bahan baku lokal seperti dedak, pollard, daun ubi kayu, biji karet dan biji kapuk sebagai bahan pakan ikan (Al Mahmud et al, 2012;Hassan et al, 2017;Deng et al, 2017;Kumar et al, 2014). Adanya faktor anti nutrisi seperti sianida, asam fitat atau serat kasar yang terlalu tinggi serta ketersediaannya yang relatif terbatas, menjadi kendala dalam memanfaatkan bahan baku darat tersebut.…”
Section: Pendahuluanunclassified